Phytochemical Profile and Antioxidant Activity of Green Onion (Allium fistulosum L.) Extract - Lis Diana Husni Putri; David Limanan; Eny Yulianti; Frans Ferdinal (International Journal of Psychology and Health Science, 2026)
Oxidative stress plays a pivotal role in the progression of various degenerative diseases due to excessive production of reactive oxygen species (ROS) that overwhelms the body's antioxidant defense system. Green onion (Allium fistulosum L.) is an herbal plant known to contain diverse bioactive compounds with potential as natural antioxidants. This study aimed to analyze the phytochemical profile and antioxidant activity of green onion extract in vitro. Extraction was performed using the percolation method with methanol. Qualitative phytochemical analysis was conducted using specific reagents. Antioxidant capacity was subsequently evaluated using DPPH, ABTS, and FRAP assays, each referenced against Trolox as the standard compound. Results showed that the extract had a yield of 20.36% and contained alkaloids, betacyanins, cardiac glycosides, glycosides, coumarins, flavonoids, phenols, quinones, saponins, steroids, terpenoids, and tannins. Antioxidant activity yielded IC₅₀ values of 185.86 µg/mL (DPPH), 91.60 µg/mL (ABTS), and 15.39 µg/mL (FRAP). These findings indicate that green onion extract possesses considerable potential as a natural antioxidant source for further development.